Stability, rheological and combustion properties of biodiesel blends with a very-low sulfur fuel oil (VLSFO). (15th May 2022) - Kass, Michael; Kaul, Brian; Armstrong, Beth; Szybist, Jim; Lobodin, Vladislav
Highlights: Biodiesel additions up to 20 wt% showed excellent blend stability with a VLSFO. Biodiesel additions up to 20 wt% improved the lubricity, viscosity and pour point of VLSFO. Biodiesel increased the estimated cetane number and eliminated the pre-existing pre-mix burn spike in the baseline VLSFO. Abstract: In this study the rheological and combustion properties were evaluated for a very low sulfur fuel oil (VLSFO) with biodiesel added at concentrations of 5, 10, 15 and 20 wt%. The samples were prepared via hand stirring, and blend uniformity was confirmed via sulfur and heat of combustion measurements. Evaluations based on the ASTM D4740 protocols confirmed blend stability (no evidence of visible asphaltene precipitation). The viscosity was significantly reduced with increased biodiesel content, while the boundary lubricity was notably improved by adding 5 wt% biodiesel. Analysis of the combustion results showed that 15–20 wt% biodiesel additions mitigated the premixed-burn spike phenomena observed for VLSFO. Biodiesel concentrations up to 15 wt% were also effective at improving the estimated cetane number and reducing the main combustion delay time and the precombustion burn period. The combination of good blend stability, reduced viscosity, and acceptable combustion properties for low blend levels suggests that biodiesel is suitable for use as a marine fuel for engines that operate on VLSFO.